PENINGKATAN HASIL BELAJAR SOAL CERITA PECAHAN DENGAN MODEL PEMBELAJARAN POLYA DI KELAS IV SD - Aisyah, Melly (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
Research of this class action aim to increase result of learning fraction story problem with the model study of polya in class of IV SD Negeri 12 Cupak Kabupatan of solok. This Matter of background by student less in comprehending the intention of the problem that is what known, to be asked and solving the story problem. So that the result of student’s learning in study of fraction is low and not yet reached KKM which have been specified by that is 70. Research of class action conducted by the kolaborasi of researcher and teacher, This research is designed by two cycle. Covering step (1) planning, (2) execution, (3) perception, (4) refleksi. The result of research show that usage of model study of polya can improve the result of learning about the fraction among the student  in the class IV SD. Keyword: hasil belajar; soal cerita pecahan; model pembelajaran polya